Perancangan Sistem Persediaan Barang Pada Bagian Penyimpanan Barang Di Cabang Pelayanan Dinas Pendapatan Daerah Provinsi Wilayah Kota Bandung III - Haris Nurdiansyah; Ali Mulyawan (Jurnal Computech & Bisnis (e-Journal), 2015)
The application program creation and use of Information System Design Inventory In Part Storage of Goods in Services Branch Provincial Revenue Office Bandung Region III aims to simplify the construction process in the office inventory with inventory application system using visual basic programming. The technique used by the technique with the concept of object-oriented systems development Object Oriented Software Enggeneering (OOSE) with an emphasis on the use case. Object Oriented Software Engineering (OOSE) is a design software and techniques used in the design of the software in object-oriented programming.  Keywords: inventory; applications; inventory information system